Mathematical simulation of heat-exchange processes in the fire tube element of hot water boiler - Stepanov, D. V.; Tkachenko, S. Y.; Bodnar, L. A. (Visnyk of Vinnytsia Politechnical Institute, 2010)
Different methods of heat exchange intensification are considered. The methods of heat exchange intensification are suggested for the fire tube boilers. The mathematical model of heat exchange intensification is developed for the fire tube element of hot water boiler of small power. The work of heat exchangers by numerical methods is studied.